2016
DOI: 10.1620/tjem.238.105
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Compromises Human Sperm Function by Reducing Intracellular cAMP

Abstract: A worldwide decline in the quality of human semen is currently occurring. In mammals, sperm are produced from diploid stem-cell spermatogonia by spermatogenesis in testes and become mature in epididymis. Nevertheless, these biological processes can be affected by Gram-negative bacterial infection mediated by lipopolysaccharide (LPS), the major endotoxin of Gram-negative bacteria. It is well known that LPS can disturb spermatogenesis and affect sperm maturation and quality in vivo. However, the effect of LPS on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The molecular actions of naturally occurring inflammation in the female genital tract on sperm functional integrity have not been reported yet. However, in in vitro studies, the mechanisms of sperm damage by LPS have been attributed to mitochondrial dysfunction and activation of oxidative phosphorylation in boars 70 , cytokine release in rabbits 63 as well as to reduction of intracellular cAMP levels in humans 71 . Survival of the sperm is further compromised by morphological alterations of the ampulla induced by inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular actions of naturally occurring inflammation in the female genital tract on sperm functional integrity have not been reported yet. However, in in vitro studies, the mechanisms of sperm damage by LPS have been attributed to mitochondrial dysfunction and activation of oxidative phosphorylation in boars 70 , cytokine release in rabbits 63 as well as to reduction of intracellular cAMP levels in humans 71 . Survival of the sperm is further compromised by morphological alterations of the ampulla induced by inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, leading to irreversible impairment of mitochondrial functions such as mitochondrial respiration, oxidative phosphorylation and transport (Bacon and Britton, 1990) ending with germ or Leydig's cell death. The most recent published results found that LPS decreased sperm intracellular cAMP in vitro leading to deleterious effect on sperm vitality by increasing dead sperm percent (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Effects of uropathogenic bacteria and LPS in the testis include inhibition of steroidogenesis and reduced androgen production [ 18 , 19 ], decreased intracellular cAMP and reduced sperm motility [ 20 ], induction of proinflammatory cytokines and activation of antimicrobial pathways [ 10 ], and epigenetic regulation of antimicrobial gene expression [ 21 ]. However, relatively little is known about interactions between regulatory pathways and mechanisms involved in the response to inflammation of the testis.…”
Section: Introductionmentioning
confidence: 99%